Determinants of exclusive breastfeeding and overall duration of breastfeeding among mothers in Plateau, Nigeria. (2021) - Emmanuel, Andy; Clow, Sheila E
Abstract : Background: It is recommended that infants should be fed exclusively with breast milk for the first 6 months, and up to 2 years after birth. This has the potential to improve child survival in limited resource settings. The aim of this study was to identify determinants of exclusive breastfeeding and overall duration of breastfeeding among pregnant mothers in Plateau, Nigeria. Method: This was a cross-sectional study involving 763 pregnant mothers attending antenatal clinics in the three senatorial districts of Plateau state, who completed a validated questionnaire. Informed consent was obtained, and all women participated voluntarily. Data were coded and analysed using Chi-square tests and logistic regression, with P <0.05 considered significant. Results: Overall, 84.4% of mothers were exclusively breastfeeding at discharge or 48 hours after birth. Exclusive breastfeeding for 6 months was practiced by 36.2% of respondents. Exclusive breastfeeding rates showed a decline as infant age increased. Women with fewer than five children were 2.3 times more likely to feed their baby other foods within the first 6 months than those with five or more children ( P =0.001). The average overall duration of breastfeeding was 15 (standard deviation±4) months. Women less than 30 years old were 2.4 times more likely to breastfeed for a shorter period of time, compared to women who were 30 years or older ( P <0.001). Chi-square analysis suggested a significant relationship between place of delivery, type of delivery, parity and infant feeding practices. Conclusions: Exclusive breastfeeding was not common among the women who participated in this study and declined with increased infant age. The overall duration of breastfeeding was 15 months, which is less than the recommended 2 years. Maternal age, place of delivery, type of delivery and parity were found to influence exclusive breastfeeding and overall breastfeeding. Understanding current practices and factors that influence breastfeeding is important to implement strategies that will empower mothers to breastfeed exclusively. Identifying the cultural practices that act as barriers to early breastfeeding is necessary for the drafting of future interventions to promote breastfeeding.